Seberapa Efektif Kearifan Lokal Berkontribusi dalam Peningkatan Kemampuan Berpikir Kritis Siswa dalam Pembelajaran IPA? - Diaz Rhamadani; Ratna Hima Taftiana; Alya Dina Ariyanto; Insih Wilujeng (Universitas Garut, 2026)
Local wisdom based science learning has emerged as an approach that effectively connects scientific concepts with cultural experiences familiar to students' daily lives. This article aims to examine the effectiveness of integrating local wisdom in enhancing students’ critical thinking skills through a literature review of 25 studies published between 2015 and 2025. The review analyzes various learning media, instructional models, and teaching materials grounded in local cultural contexts across different educational levels. The findings reveal that local wisdom plays a significant role in improving the relevance and comprehension of science concepts while fostering higher-order thinking skills, including analyzing, evaluating, and drawing conclusions. Learning activities linked to cultural practices increase students’ cognitive engagement because the content becomes more meaningful and easier to relate to real-life experiences. The novelty of this article lies in its comprehensive cross-level synthesis, demonstrating that local wisdom not only enhances critical thinking at a single grade level but also contributes progressively from elementary to senior high school. This article contributes to strengthening the theoretical foundation of cultural integration in science learning and provides practical insights for teachers to design contextual and meaningful instruction.Keywords: critical thinking, ethnoscience, LKPD, local wisdom, science education